Kajian faktor threat dan coping terhadap partisipasi wanita dalam program skrining kanker leher rahim - Nurul Ahdani, Mohammad Hakimi dan Suharyanto Supardi (Berita Kedokteran Masyarakat (BKM), 2004)
Backgrounds: In developing countries, including Indonesia, 80-90 percent cancer patients are usually incurable because it is already in late stadium. if it is found in an early stage, more than half of it could be cured. Screening program of cervical cancer is aimed at reducing the mortality rate caused by cancer. Therefore, active participation of women is expected as the threat of cervical cancer is considered as the number one among types of cancer that affect women. In fact, Pap smear test has not yet become a need. This causes low participation of women in the screening program of cervical cancer. Objectives: To appraise the association between threat and coping factors with women participation in the screening program of cervical cancer in the Bureau of Cancer Consultation Kucala Foundation Yogyakarta. Methods: This is an observational study with case control study design. The subjects of this study were women who did pap smear test (screening) for the first time in Kucala Foundation during the of October 2003 to the 10'h of January 2004 that were considered as cases and their neighbor considered as controls. The subjects consisted of 68 cases and 68 controls (1:1). The examined dependent variable was women participation in the screening of cervical cancer. Independent variables were intrinsic rewards, extrinsic rewards, perception of severity, perception of vulnerability, response efficacy, self efficacy and response cost. Data were analyzed in univariate, stratification and multivariate methods. Results: The result of this study showed that all independent variables had significant relationship